Back to Tlalocan: deities, activism and ancestral symbols of water in Mesoamerican art today - Santos, Renata Ribeiro dos (Farol, 2025)
This text proposes a reflection on the reactivation of ancestral knowledge, especially of Mexica origin, related to water—a central element in Indigenous worldviews—based on some contemporary art and architecture proposals developed in the Mesoamerican region, with a focus on Mexico. These works evoke aquatic deities and ancient sustainable technologies, establishing dialogues with contemporary climate and Indigenous activism. The research seeks connections between works that incorporate symbols, myths, and traditional techniques as a way of denouncing environmental issues. To this end, it adopts analytical tools from postcolonial, feminist, and visual studies. These approaches are grounded in historical and cultural references from the original civilizations, expanding the understanding of creative processes and their social and ecological repercussions.